Shelf Transport Pathways Adjacent to the East Australian Current Reveal Sources of Productivity for Coastal Reefs - Roughan, Moninya; Cetina-Heredia, Paulina; Ribbat, Nina; Suthers, Iain M. (Frontiers in Marine Science, 2022)
The region where the East Australian Current (EAC) separates from the coast is dynamic and the shelf circulation is impacted by the interplay of the western boundary current and its eddy field with the coastal ocean. This interaction can drive upwelling, retention or export. Hence understanding the connection between offshore waters and the inner shelf is needed as it influences the productivity potential of valuable coastal rocky reefs. Near urban centres, artificial reefs enhance fishing opportunities in coastal waters, however these reefs are located without consideration of the productivity potential of adjacent waters. Here we identify three dominant modes of mesoscale circulation in the EAC separation region (31.5-34.5S); the ‘EAC mode’ which dominates the flow in the poleward direction, and two eddy modes, the ‘EAC eddy mode’ and the ‘Eddy dipole mode’, which are determined by the configuration of a cyclonic and anticyclonic eddy and the relationship with the separated EAC jet. We use a Lagrangian approach to reveal the transport pathways across the shelf to understand the impact of the mesoscale circulation modes and to explore the productivity potential of the coastal waters. We investigate the origin (position and depth) of the water that arrives at the inner-mid shelf over a 21-day period (the plankton productivity timescale). We show that the proportion of water that is upwelled from below the euphotic zone varies spatially, and with each mesoscale circulation mode. Additionally, shelf transport timescales and pathways are also impacted by the mesoscale circulation. The highest proportion of upwelling (70%) occurs upstream of 32.5S, associated with the EAC jet separation, with vertical displacements of 70-120~m. From 33-33.5S, water comes from offshore above the euphotic layer, and shelf transport timescales are longest. The region of highest retention over the inner shelf is immediately downstream of the EAC separation region. The position of the EAC jet and the location of the cyclonic eddy determines the variability in shelf-ocean interactions and the productivity of shelf waters. These results are useful for understanding productivity of temperate rocky reefs in general and specifically for fisheries enhancements along an increasingly urbanised coast.